EXPLORING THE CORRELATION BETWEEN STUDENTS' PERCEPTIONS AND ACHIEVEMENTS ON ENGLISH ONLINE HOMEWORK - Tiara Vagari; Slamet Asari; Nirwanto Maruf (British (Jurnal Bahasa dan Sastra Inggris), 2023)
This research investigates the correlation between students' perceptions of English online homework and their corresponding achievements, aiming to shed light on the interplay between these variables. A correlational research design was employed, involving 187 secondary school students from SMP YIMI 'FDS' Gresik. Data on perceptions and achievements exhibited normal distribution and significance levels (2-tailed) below 0.05, affirming the robustness of the study. The Spearman correlation test unveiled a very strong correlation between students' positive perceptions of online homework and their English achievements. The findings align with previous studies, emphasizing the pivotal role of attitudes in shaping academic outcomes. The outcomes resonate with Self-Determination Theory, suggesting that fostering favorable perceptions can enhance intrinsic motivation and learning outcomes. The study underscores the significance of user-friendly instructional design and a balanced approach to learning. It also recognizes limitations related to sample and cross-sectional design. In conclusion, the research contributes to understanding the impact of students' perceptions on their achievements in the digital learning era, urging educators to prioritize not only technological integration but also the psychological dimensions of education.